Pengaruh Penggunaan Model Problem Based Learning pada Materi Siaga Bencana terhadap Kemampuan Literasi Sains Siswa Kelas IV SD Negeri Kota Bengkulu - Rizqa Dwi Shofiya Maghfira Izzania; Endang Widi Winarni; Neza Agusdianita (JURIDIKDAS, 2020)
This  study  aims  to  determine  the  effect  of  the  use  of  the  Problem  Based Learning model on disaster preparedness material on the  scientific literacy skills of Class IV students at the Bengkulu State Elementary School. This type of research is quantitative research with experimental methods. The design in this study is The Matching Only Pretest-Postest Group Design. The population in this study was SDN 01, SDN 04, SDN 08, and SDN 11. The sampling used cluster random sampling technique so that the fourth grade of SD Negeri 08 Bengkulu City (experimental class) and class IVA SD Negeri Bengkulu City (control class) were obtained. Instrument testing was conducted in class V of SD Negeri 04 Kota Bengkulu. The instruments used in this study were the questionnaire  components  of  scientific  attitude  totaling  15  questions,  the multiple-choice  context  sheet  test  sheets  totaling  10  questions.  Soft  test components  in  the  form  of  multiple  choice  knowledge  which  number  10 questions, and observation sheets of competency components. The calculation results of the t-test gain score on the components of scientific attitude obtained a thitung of 5.73 greater than the ttabel value of 1.673, in the context component obtained a thitung of 4.48 greater than the ttabel value of 1.673, the component of knowledge obtained by thitung for 4.78 greater than the ttabel value of 1.673, and in the competency component in the experimental class the criteria are very good at 57%, the criteria for good are 43% while the criteria for the control class are very good at 35.7%, the criteria are good 53.6% , the criteria are quite 10.7%. Based on the results of the four components of scientific literacy, it means that there is a significant influence on the use of the Problem Based Learning model on students' literacy skills. The conclusion in this study is that there is the influence  of  the  use  of  the  Problem  Based  Learning  model  in  Disaster Preparedness  material  on  Science  Literacy  Ability  of  Class  IV  Students  of Bengkulu City Elementary School.Keywords:   Problem  Based  Learning  Model,  Disaster  Preparedness,  Science, Literacy Ability